On Jumped Wenger Graphs (Communications in Mathematical Research, 2022)
We introduce a new infinite class of bipartite graphs, called jumpedWenger graphs, which has a similar structure with Wenger graphs. We givea tight upper bound of the diameter for these graphs and the exact diameterfor some special graphs. We also determine the girth of the jumped Wengergraphs.